THE INFLUENCE OF TAX AVOIDANCE AND ESG PERFORMANCE ON RIIL EARNINGS MANAGEMENT WITH CARBON TAX MODERATOR - Laiman, Sean Jonathan; Handoko, Jesica (Jurnal Aplikasi Akuntansi, 2026)
This study investigates the influence of tax avoidance and Environmental, Social, and Governance (ESG) performance on real earnings management while examining the moderating roles of carbon tax exposure and ESG Leader status. Unlike accrual-based earnings management, real earnings management is more difficult to identify and may cause persistent distortions in firms' operational decisions, making it a critical focus of this study. This study employs a quantitative research design using secondary data derived from the annual financial statements and sustainability reports of companies listed on the Indonesia Stock Exchange. The research sample comprises 45 firms with the highest ESG ratings included in the IDX Kehati Index over the 2022–2024 period. The data were analyzed using linear regression with moderation testing. The empirical findings reveal that tax avoidance has a negative and significant effect on real earnings management, indicating that firms engaging in higher tax avoidance tend to exercise greater caution in manipulating real activities, possibly because of heightened regulatory oversight. In contrast, ESG performance does not exhibit a significant relationship with earnings management, suggesting that ESG implementation among Indonesian public companies may remain symbolic rather than substantively embedded in accounting and operational policies. Carbon tax exposure significantly moderates the relationship between tax avoidance and earnings management by reversing the relationship in a positive direction, implying that increased cost pressures from carbon regulation encourage firms to intensify earnings management as a strategic response. However, the carbon tax does not moderate the association between ESG performance and earnings management, indicating a lack of integration between sustainability initiatives and regulatory mechanisms. Furthermore, ESG Leader status does not moderate the effects of tax avoidance or ESG performance on earnings management.